INOVASI PELAKSANAAN DETEKSI DINI PENYAKIT TIDAK MENULAR DENGAN “ATASI PENYAKIT TIDAK MENULAR DENGAN PATRANG” - Sulton Wariin; Ika Mardiyah Bratajaya; Pradhika Ghozi Syamsiar; Tantut Susanto; Adhita Fitrina Andiani (LPPM Universitas dr. Soebandi, 2024)
Non-communicable diseases (NCDs) are long-term illnesses. One of them is hypertension. Risk factors for NCDs include lifestyle, diet, physical activity and genetic factors. Handling NCDs requires special attention, including basic health services that are affordable and easily accessible. Implementation of early detection of PTM has been carried out at the Patrang Community Health Center, but the implementation has not been effective because the implementation process takes too long. The method used is to summarize the flow and bring the early detection post closer to other inspection location elements. The innovation of OVERCOMING noncommunicable diseases with PATRANG is one solution for implementing early detection of non-communicable diseases. The results of community service show that the implementation of early detection with this innovation is effective and there is an increase in patient satisfaction with the NCD detection innovation service.